MILITARY INCLUSION AND REHABILITATION: CREATING A UNIFIED APPROACH TO VETERAN RECOVERY, INTEGRATION, AND SUPPORT - Sopilko, Iryna (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
The purpose of the scientific article is to summarize the results of an expert meeting at the National Defense University of Ukraine with the results of research on the inclusion and rehabilitation of military personnel, as well as to develop proposals for creating a unified approach to the recovery, integration and support of veterans. This includes determining the main areas of rehabilitation programs, improving social adaptation mechanisms and creating conditions for the effective integration of military personnel into civilian life. Taking into account the specifics of this problem, the article also considers the role of state and non-governmental organizations in supporting veterans, as well as the importance of international experience for improving national programs. Methods: to achieve the goal, general and special scientific methods were used, in particular: analysis, synthesis, induction, deduction, concretization, abstraction and comparison. These methods allowed to collect various approaches to the rehabilitation of veterans and develop proposals for improving existing practices. Results: the analysis showed that the inclusion and rehabilitation of military personnel are complex in nature, including medical, psychological and social support. The developed proposals contribute to improving the integration of veterans through professional retraining, socialization and access to social services. Attention is also focused on the need to create a unified rehabilitation system that combines medical and social aspects, and on the importance of integrating international experience to ensure effective support for veterans. An important component is raising public awareness of the problems of veterans and reducing the stigma they face after returning to civilian life. Discussion: when analyzing the results of rehabilitation programs for veterans, it is worth paying attention to the need to specify the topics of rehabilitation and social integration, as well as to coordinate different approaches between state and non-governmental organizations. It is important to create coordination mechanisms for integrating different types of assistance to veterans in order to ensure their full adaptation to civilian life. In addition, it is necessary to take into account the specifics of each veteran and individual needs, which may vary depending on the injuries received, professional training and social environment.